2017
DOI: 10.1111/bjd.15790
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an association between alcohol intake and an increased risk of nonmelanoma skin cancer

Abstract: Linked Article: Yen et al. Br J Dermatol 2017; 177:696–707.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several mechanisms have been attributed to this increased risk of breast cancer (Chen et al, 2011).Abnormal estrogen levels have been associated with breast cancers, and alcohol intake increases circulating sex hormone levels in both premenopausal (Reichman et al, 1993) and postmenopausal women (Dorgan et al, 2001). The proposed mechanisms include increased aromatase activity (Purohit, 2000), decreased hepatic catabolism of androgens (Sarkola et al, 2001), and/or effects on adrenal steroid production (Dorgan et al, 2001) Alcohol intake has also been linked to an increase in several other cancers, such as gastric cancer (Tramacere et al, 2012), colorectal cancer (Fedirko et al, 2011), liver cancer (Bagnardi et al, 2015),prostate cancer (Watters et al, 2010), lung cancer (Bagnardi et al, 2015), and some skin cancers (Rota, 2017). It also increases the risk of an aero digestive-tract cancer (Day et al, 1994).In a review of 222 articles in 2013, (comprising of about 92,000 light drinkers and 60,000 non-drinkers with cancer) Bagnardi and group (2013) found that light drinking increases the risk of or pharyngeal cancer by 17%; esophageal squamous cell carcinoma by 30%, and breast cancer by 5%.…”
Section: Alcoholismmentioning
confidence: 99%
“…Several mechanisms have been attributed to this increased risk of breast cancer (Chen et al, 2011).Abnormal estrogen levels have been associated with breast cancers, and alcohol intake increases circulating sex hormone levels in both premenopausal (Reichman et al, 1993) and postmenopausal women (Dorgan et al, 2001). The proposed mechanisms include increased aromatase activity (Purohit, 2000), decreased hepatic catabolism of androgens (Sarkola et al, 2001), and/or effects on adrenal steroid production (Dorgan et al, 2001) Alcohol intake has also been linked to an increase in several other cancers, such as gastric cancer (Tramacere et al, 2012), colorectal cancer (Fedirko et al, 2011), liver cancer (Bagnardi et al, 2015),prostate cancer (Watters et al, 2010), lung cancer (Bagnardi et al, 2015), and some skin cancers (Rota, 2017). It also increases the risk of an aero digestive-tract cancer (Day et al, 1994).In a review of 222 articles in 2013, (comprising of about 92,000 light drinkers and 60,000 non-drinkers with cancer) Bagnardi and group (2013) found that light drinking increases the risk of or pharyngeal cancer by 17%; esophageal squamous cell carcinoma by 30%, and breast cancer by 5%.…”
Section: Alcoholismmentioning
confidence: 99%